As cooperativas e o Plano de Desenvolvimento Nacional K'atun: Nossa Guatemala 2032. O caminho para o triplo balanço do desenvolvimento econômico, social e ambiental - Ovando Chán, Victor René (2021)
The analysis has shown that cooperative companies are the ones that best satisfy all dimensions of sustainable development, responding to economic, social and environmental problems. However, there are numerous institutional, political and discriminatory treatment challenges that must be faced in national legislation, as a result of the lack of understanding about the real and potential contribution of cooperatives to the fulfillment of the goals set out in the National Development Plan K´atun: Our Guatemala 2032. In this context, this research sought to establish the intrinsic correlation between the cooperative movement and the achievement of the goals set out in the National Development Plan K´atun: Guatemala 2032.